2012
DOI: 10.4103/0974-9233.95248
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness in Iranian congenital glaucoma patients

Abstract: Purpose:To compare central corneal thickness (CCT) in subjects with controlled primary congenital glaucoma (PCG) and nonglaucomatous subjects and to investigate the correlation between CCT and intraocular pressure (IOP) in the study population.Materials and Methods:Twenty-three consecutive PCG cases with controlled IOP and no clinical evidence of corneal edema comprised the Study Group. There was an interval of at least 2 months between last intraocular surgery and inclusion in the study. Twenty-one subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
13
1
2
Order By: Relevance
“…On the other hand, other studies reported significantly thicker CCT in patients with PCG 8,22,23. Corneal thickening in congenital glaucoma could be an inherent component of the pathophysiology and related to racial and genetic background.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, other studies reported significantly thicker CCT in patients with PCG 8,22,23. Corneal thickening in congenital glaucoma could be an inherent component of the pathophysiology and related to racial and genetic background.…”
Section: Discussionmentioning
confidence: 87%
“…Corneal thickening in congenital glaucoma could be an inherent component of the pathophysiology and related to racial and genetic background. Alternately, the thicker cornea could be due to the presence of subclinical corneal edema as a result of endothelial dysfunction and long-lasting IOP elevation 23. Oberacher-Velten et al22 concluded that even apparently clear corneas under high IOP in congenital glaucoma might have subclinical edema.…”
Section: Discussionmentioning
confidence: 99%
“…Daneshvar et al. () reported thicker corneas in patients with PCG and suggested the cause to be corneal oedema or endothelial dysfunction. Most other studies have reported significant corneal thinning in PCG as compared to control eyes (Henriques et al.…”
Section: Discussionmentioning
confidence: 99%
“…Большинство авторов, отмечая это обстоятельство, вместе с тем сообщают, что еди-ное мнение по поводу динамики центральной тол-щины роговицы при врождённой глаукоме пока отсутствует [13,16,25,26,30,36,40,44,54,56,57]. Более подробно эти сведения рассмотре-ны ниже.…”
Section: Doi: 1017816/ov9323-31unclassified
“…Так, H. Amini et al (2012) определили, что у детей с первичной врождённой глаукомой (при условии нормализации ВГД) определяется даже несколько более «толстая» роговица, чем у здоровых детей аналогичного возраста и пола (589,42 ± 53,44 и 556,14 ± 30,51 мкм соответ-ственно) [13]. Кроме того, K.W.…”
Section: Doi: 1017816/ov9323-31unclassified